"I see enough queers walking the streets in this city": Homosexuality and Sexual Geographies in Black Consumer Magazines during the 1970s. Issue 2 (1st October 2016) - West, E. James
Abstract : This article examines the representations of black homosexuality during the 1970s in Ebony and Jet, America's most popular black periodicals. As two of the most important "indigenous information sources" available to black communities during this period, Ebony and Jet played a critical role in shaping broader public perceptions and anxieties over black respectability, queer identity, and homosexual desire. Through the contributions of predominantly heterosexual and male "experts" such as Alvin Poussaint and Winston Moore, these magazines helped to reinforce pervasive fears regarding the potential "threat" posed by homosexuality to black families and black communities, and contributed to a broader policing of nonheteronormative desire within black urban spaces. However, many of the magazines' readers offered a more progressive vision of homosexuality and its relationship to the black community, and attempted to redefine the public boundaries of black respectability. Through addressing the complex intersections of race, respectability and physical space, this article provides a fresh insight into the spatialization of black sexual and gender minorities within black popular print culture, and the highly contested "geographies of black gender and sexual marginality."